Discontent with content analysis of online transcripts - Judith Guevarra Enriquez (Association for Learning Technology, 2009)
Content analysis has dominated computer-mediated communication and educational technology studies for some time, and a review of its practices applied to online corpus of data or messages is overdue. We are confronted with complexity given the various foci, nuances and models for theorising learning and applying methods. One common suggestion to deal with the complexity in content analysis is a call for standardisation by replication or systematic research studies. This article presents its ‘discontent' with content analysis, discussing the issues and concerns that surround the analysis of online transcripts. It does not attempt to resolve nor provide a definitive answer. Instead, it is an open inquiry into another way of looking at online content. It presents an alternative or perhaps an extension of what we have come to know as content analysis. It argues for the notion of genres as another way of conceptualising online transcripts. It proposes two things: first that in performing transcript analysis, it is worthwhile to think how messages relate to a system of interactions that persists even beyond the online environment; secondly, there is an emergent and recurring metastructuring that is at work in online environments that is worth exploring, instead of imposing structures – models and frameworks that do not fit the emerging communicative practices of participants.